FACTORS AFFECTING DECISION MAKING IN BUYING HALAL FOOD PRODUCTS - WIRIYA BOONMALERT, วิริยา บุญมาเลิศ; KOMSON SOMANAWAT, คมสัน โสมณวัตร (Dusit Thani College Journal, 2018)
This research on consumers and their selection behavior in buying halal food products has the following objectives: 1) To study the relationship between the cause factors of the products and the selection behavior in buying halal food products, 2) To test the cause coherence of association between the model constructed and empirical data, and 3) To study direct and indirect influential factors affecting the selection in buying halal food products. Statistics used in data analysis are Average, Percentage, Frequency, Standard Deviation, t-test, One Way ANOVA. The research results indicated that sample groups were 178 males representing 44.5 percent of the whole samples and 222 females representing 55.5 percent. On samples, 102 samples, were over 41 years of age representing 25.50 percent, 147 samples were undergraduate representing 36.75 percentage, 228 samples were married representing 57.00 percent, 138 samples were single representing 34.50 percent, 109 samples earned between 10,001-15,000 baht per month representing 27.25 On selection in buying halal food products, it revealed that sample groups chose to buy products with halal sign highest at 87.25 percent, next to that was regulation given in accordance with religious principles at 82.25 percent, and it was found that sample groups chose to buy products with popular brand names in Thailand at 88.75 percent, and chose to buy products with imported brands at 11.25 percent, family was influential to the selection to buy the products highest at 62.50 percent, next to that, advertisement was second at 21.75 percent. On information resource relating to halal food products, the research results revealed that most samples received information from relatives/friends at 75.25 percent; they bought raw materials for food recipes such as vegetables, meat, highest at 64.50 percentage; on shop location that halal food products were bought, fresh market was rated the highest at 54.75 percent; on distribution model for halal food products, it was found that most halal food products were bought in places with convenience the highest at 71.75 percent; and on promotional activities that sellers of halal food products should arrange, it was found that samples wanted promotional activities with discount on the products the highest at 73.75 percent . The research results on attitude factors revealed that production procedure in accordance with Islamic religious regulations was rated highest (Mean= 4.64), on product factors revealed that quality, new and fresh, wide variety for selection, and display of Halal Guarantee sign, were equally rated highest (Mean = 4.66) in that order.